Launch! Advertising and Promotion in Real Time - Solomon, Michael; Cornell, Lisa Duke; Nizan, Amit (Open textbook library., 2009)
Launch! Advertising and Promotion is written for advertising and promotion courses taught to students in the business school and journalism & mass communication students. This textbook is the first of its kind to teach advertising concepts by reverse engineering a real advertising campaign from beginning to end. In April 2007, SS+K, an innovative New York City communications agency, launched the first ever branding campaign for msnbc.com with the tag "A Fuller Spectrum of News." Launch! follows that campaign from initial agency pitch through roll-out of print and media assets to post-campaign analysis. Throughout, it exposes readers to the theory and concepts of advertising and promotion, and the personalities and decisions that drove this campaign. The book takes a rare look ”behind the curtain“ — even letting you see some of the paths not chosen by the agency and client. Students get a realistic sense of how theory plays out in practice, and get a flavor for the exciting field of advertising and promotion. And, they consistently learn the perspectives of both the advertising agency (where many journalism and communications students will work) and the client (where many marketing majors will work). This is a unique book, with a unique perspective, by a unique author team, and you won't find this kind of insight in any other text on the market. We think you're going to love it! This textbook has been used in classes at: Ball State University, Emerson College, Florida Institute of Technology, Grand Valley State University, Johnson County Community College, Manchester Business School, McLennan Community College, Michigan State University, North Hennepin Community College, Pierce College, Rochester Institute of Technology, Saint Louis University, Salem State College, South Dakota State University, Texas State University, Texas Tech University, University of New Hampshire, University of North Carolina, University of Notre Dame, University of South Florida, Virginia Tech, Western Kentucky University.